PENGARUH SERVICE QUALITY, PRODUCT QUALITY DAN CUSTOMER EXPERIENCE TERHADAP KEPUASAN KONSUMEN PADA TOKO ROTI ZAHRA BAKERY AND CAKE DI KOTA KISARAN - Dinda Sri Rahmadani; Zulfa Khairina Batubara (Smart Education, 2026)
This study aims to determine the simultaneous and partial effects of service quality, product quality, and customer experience on consumer satisfaction. The sample consisted of 96 respondents. The data analysis technique used multiple linear regression. The regression results produced the equation: Y = 1,901 + 0,315X1 + 0,561X2 + 0,407X3. The F-test result shows an Fcount (33.997) > Ftable (2.70), indicating that service quality, product quality, and customer experience simultaneously have a significant effect on consumer satisfaction. The t-test results show that, partially, service quality has a positive effect on consumer satisfaction because tcount (2.145) > ttable (1.986), product quality has a positive effect on consumer satisfaction because tcount (6.240) > ttable (1.986), and customer experience also has a positive effect on consumer satisfaction because tcount (3.386) > ttable (1.986). The R² test result shows an Adjusted R Square value of 0.510, meaning that the independent variables consisting of service quality, product quality, and customer experience are able to explain consumer satisfaction by 51%, while the remaining 49% is explained by other variables not included in this study.